Kekuasaan dan Konflik Dalam Organisasi - Eka Susanti; Adelia Rahma; Rahma Laila Tambunan; Khairiah Zahara; Muammar Suharso (Lembag, 2024)
This research aims to understand the dynamics of power and conflict in organizations through a qualitative study. Data was collected through participant observation, in-depth interviews, and document analysis at a manufacturing company in Indonesia. The research results show that power in organizations is complex and multidimensional, with various sources and forms. Conflict arises as a consequence of struggles over resources, differences in interests, and disagreements about norms and values. This research contributes to the understanding of how power and conflict are interrelated in organizations. These findings also provide implications for management practice, highlighting the importance of effective leadership, open communication, and fair conflict resolution mechanisms.